PEDAGOGY OF ONLINE EDUCATION IN TEACHER EDUCATION COLLEGES DURING COVID 19 PANDEMIC - Palakunnathu, Dr. Padma Priya P V (International Journal of Research -GRANTHAALAYAH, 2023)
The COVID 19 pandemic has wreaked havoc on education systems around the world affecting approximately 825 million learners. More than 94 percentage of the world’s student population has been affected by the indefinite closure of educational institutions. This has resulted in significant changes in every aspect of human life. This paper focuses on the Teacher Education sector; teacher education institutions and the various strategies adopted by teacher educators to tide over an unplanned and forced shift from face to face to online education. Teacher educators had to envisage new learning environments for student teachers, the prospective teachers, taking into account the requirements of teacher education programmers’ as well as the conditions in which both the universities and schools have to function. This paper intends to examine the various forms of online teaching modes adopted by colleges of teacher education, affiliated to different universities of Kerala state during covid-19 pandemic and throws light on the effect of conducting practice teaching sessions through online mode in enhancing teaching competencies among student teachers. The method adopted for the present study is the Normative Survey method in which the perception of 50 teacher educators were taken into account and samples were selected through random sampling technique. The findings of the study clearly give notions regarding the various online teaching modes adopted by teacher education colleges during COVID19 Pandemic like, Google meet, zoom, slack, Cisco, WebEx, and configurable cloud-based learning management solutions like Moodle, Skype, and big blue button as well as the challenges faced by student-teachers while conducting practice teaching sessions through online mode. Analysis of the data makes it clear that among the selected 7 core teaching skills and their components skills, acquisition of skill of stimulus variation, skill of probing questions and skill of reinforcement were not effective when student- teachers practiced the same through online mode as per the perception of teacher- educators. At the same time, acquisition of skill of introduction, skill of explaining, skill of illustrating with examples and skill of achieving closure were very effective according to the perception of teacher educators.